Effects of Pre-emptive Aortic Side Branch Embolization on Early-Stage Type II Endoleaks and Sac Changes After Endovascular Aneurysm Repair for Abdominal Aortic Aneurysm - Hyeonju Kim; Deokbi Hwang; Seung Huh; Woo-Sung Yun; Hyung-Kee Kim (Vascular Specialist International)
Purpose: This study evaluated the effect of pre-emptive embolization of the aortic side branches on the short-term incidence of type II endoleaks (T2ELs) and aneurysm sac changes following endovascular aneurysm repair (EVAR) of abdominal aortic aneurysms (AAAs). Materials and Methods : Data of 157 patients with degenerative large AAAs (≥50 mm for males and ≥45 mm for females) treated between January 2019 and October 2024 were retrospectively analyzed. The patients were categorized into the pre-emptive embolization (n=30, 19.1%) and non-embolization (n=127) groups. Embolization was considered for patients with high-risk factors for T2EL, specifically an inferior mesenteric artery (IMA) diameter ≥3 mm and a large lumbar artery diameter. Outcomes were assessed 1 month and 1 year postoperatively. The primary outcome was T2EL incidence, and the secondary outcomes were changes in aneurysm size and reintervention rates. Results : At 1 month postoperatively, T2EL incidence was significantly lower in the embolization group (3.3%, 1/30) than in the non-embolization group (22.8%, 29/127) (P=0.015). At 1 year postoperatively, the T2EL incidence was 8.0% (2/25) in the embolization group and 23.0% (23/100) in the non-embolization group, although the difference was not statistically significant (P=0.094). Sac expansion was absent in the embolization group, whereas 4.0% of patients in the non-embolization group experienced expansion (P=0.583). Subgroup analysis for 37 patients with patent IMA ≥3 mm showed a significantly lower T2EL incidence at 1 month (5.6% vs. 52.6%, P=0.002) and 1 year (12.5% vs. 52.9%, P=0.014) postoperatively in the embolization group. Additionally, sac shrinkage was higher in the embolization group than in the non-embolization group (56.2% vs. 23.5%, P=0.055). Multivariable analysis confirmed pre-emptive embolization as an independent protective factor for T2EL at 1 year postoperatively (odds ratio 0.071, 95% confidence interval, 0.008-0.663; P=0.020). Conclusion : Pre-emptive embolization reduced the incidence of early T2EL after EVAR and showed stable outcomes at the 1-year follow-up, particularly in patients with large patent IMA diameters.